On the predictive power of the Malaysian T bills term spread in predicting real economic activity - Ghazali, Noor Azlan; Soo, Wah Low (Universiti Utara Malaysia, 1999)
The ability of financial market interest rates to predict real economic activity has gained considerable attention of economics and financial researchers. In this regard, the term spread, i.e. the difference between long term and short term yield is argued to be an effective indicator to predict economic cycle. We investigate this proposition for the Malaysian economy using the T bills discount rates. Our results of both, single and multi-equation system of vector autoregression (VAR), support the case for Malaysia Current T bills spread is shown to be a significant indicator for annual output growth for up to six months ahead. We also show that information conveyed by the term spread is unique and not of those implied by the monetary policy. Our results also indicate that, the power of term spread is limited for the near term predicition and over the long run money dominates spread in predicting output.